Long-term drug modification to the surface of mesenchymal stem cells by the avidin-biotin complex method. Issue 1 (December 2017) - Takayama, Yukiya; Kusamori, Kosuke; Hayashi, Mika; Tanabe, Noriko; Matsuura, Satoru; Tsujimura, Mari; Katsumi, Hidemasa; Sakane, Toshiyasu; Nishikawa, Makiya; Yamamoto, Akira
Abstract Mesenchymal stem cells (MSCs) have various functions, making a significant contribution to tissue repair. On the other hand, the viability and function of MSCs are not lasting after anin vivo transplant, and the therapeutic effects of MSCs are limited. Although various chemical modification methods have been applied to MSCs to improve their viability and function, most of conventional drug modification methods are short-term and unstable and cause cytotoxicity. In this study, we developed a method for long-term drug modification to C3H10T1/2 cells, murine mesenchymal stem cells, without any damage, using the avidin-biotin complex method (ABC method). The modification of NanoLuc luciferase (Nluc), a reporter protein, to C3H10T1/2 cells by the ABC method lasted for at least 14 daysin vitro without major effects on the cellular characteristics (cell viability, cell proliferation, migration ability, and differentiation ability). Moreover, in vivo, the surface Nluc modification to C3H10T1/2 cells by the ABC method lasted for at least 7 days. Therefore, these results indicate that the ABC method may be useful for long-term surface modification of drugs and for effective MSC-based therapy.